2013
DOI: 10.1186/1471-2350-14-17
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between a functional variant of the BRCA-1 related associated protein (BRAP) gene and ischemic stroke

Abstract: BackgroundAtherosclerosis shares common pathogenic features with myocardial infarction (MI) and ischemic stroke. BRCA-1 associated protein (BRAP), a newly identified risk gene for MI, aggravates the inflammatory response in atherosclerosis. The aim of this study was to test the association between the BRAP gene and stroke in a Taiwanese population.MethodsA total of 1,074 stroke patients and 1,936 controls were genotyped for the functional SNP rs11066001. In our previous studies, the rare allele of this SNP has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…In fact, reduced capability for endothelial repair [23, 30] and hypertension [2] characteristic of short stature might perform an important role in the incidence of stroke for participants with short stature. Since BRAP is reportedly associated with atherosclerosis [15] but not associated with stroke [16] and SNPs (rs3782886) are associated with short stature [14], SNP (rs3782886) might perform an import function for the prevention of stroke for participants with short stature by stimulating endothelial repair. In the present study, even though SNP (rs3782886) was found to be associated with a high platelet count, which is related to hypertension, no significant association between SNP (rs3782886) and hypertension was observed, which partly supports the aforementioned mechanisms because adequate endothelial maintenance was performed predominantly for normal body weight participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, reduced capability for endothelial repair [23, 30] and hypertension [2] characteristic of short stature might perform an important role in the incidence of stroke for participants with short stature. Since BRAP is reportedly associated with atherosclerosis [15] but not associated with stroke [16] and SNPs (rs3782886) are associated with short stature [14], SNP (rs3782886) might perform an import function for the prevention of stroke for participants with short stature by stimulating endothelial repair. In the present study, even though SNP (rs3782886) was found to be associated with a high platelet count, which is related to hypertension, no significant association between SNP (rs3782886) and hypertension was observed, which partly supports the aforementioned mechanisms because adequate endothelial maintenance was performed predominantly for normal body weight participants.…”
Section: Discussionmentioning
confidence: 99%
“…Single-nucleotide polymorphism (SNP) (rs3782886) in breast cancer suppressor BRCA1-related associated protein (BRAP) is reportedly associated with risk of myocardial infarction [13], while SNP (rs3782886) is also found to be associated with short stature in a previous study by us [14]. Another study reported that BRAP activates inflammatory cascades and increases the risk of carotid atherosclerosis [15] but is not associated with risk of stroke [16]. Although an SNP (rs3782886) could be associated with carotid atherosclerosis, these studies indicate that it might also have a beneficial effect on stroke prevention by inducing endothelial repair in participants with short stature; otherwise, these participants would have high risks of hypertension [2], carotid atherosclerosis [3], and stroke [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, identification of dysregulated pathways was proposed as possible biomarkers for such disorders [43, 44]. This study conferred a strong evidence of similarities on the pathogenesis between insulin resistance and atherosclerosis, which could support diagnostic processes and drug design in a more effective manner facilitating a more personalized medicine in patients with metabolic syndrome.…”
Section: Discussionmentioning
confidence: 90%
“…Japanese individuals are characterized by higher rates of stroke than myocardial infarction 27 . Even SNPs in BRAP have been reported to be associated with the risk of myocardial infarction 2 , but not with stroke 28 . As such, genetic factor has the potential to have a strong beneficial influence on preventing hypertension, especially in the Japanese population, which has a higher risk of stroke.…”
Section: Discussionmentioning
confidence: 99%